2015
DOI: 10.1371/journal.ppat.1004657
|View full text |Cite
|
Sign up to set email alerts
|

Human Adenovirus 52 Uses Sialic Acid-containing Glycoproteins and the Coxsackie and Adenovirus Receptor for Binding to Target Cells

Abstract: Most adenoviruses attach to host cells by means of the protruding fiber protein that binds to host cells via the coxsackievirus and adenovirus receptor (CAR) protein. Human adenovirus type 52 (HAdV-52) is one of only three gastroenteritis-causing HAdVs that are equipped with two different fiber proteins, one long and one short. Here we show, by means of virion-cell binding and infection experiments, that HAdV-52 can also attach to host cells via CAR, but most of the binding depends on sialylated glycoproteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 59 publications
6
72
0
1
Order By: Relevance
“…Specifically the SSF interacts with SA. Structure function analysis revealed that the SA interface is on the side of the trimeric short fiber knob rather than in the central cavity as is the case for HAdV-37 [36].…”
Section: Large-scale Approaches To Study Early Virus-host Cell Interamentioning
confidence: 89%
See 2 more Smart Citations
“…Specifically the SSF interacts with SA. Structure function analysis revealed that the SA interface is on the side of the trimeric short fiber knob rather than in the central cavity as is the case for HAdV-37 [36].…”
Section: Large-scale Approaches To Study Early Virus-host Cell Interamentioning
confidence: 89%
“…HAdV-52 is equipped with two different fibers, SSFs and LSFs. The SSF binds to polysialic acidcontaining glycans, but through a different pocket than that in the knob of HAdV-37 [36,37]. In addition, several non-human AdV types can also bind to SAcontaining glycans [38][39][40].…”
Section: Sa-containing Glycansmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the host cell surface Sia by NA treatment abolished HAdV-G52 binding to and infection of Sia-expressing original Chinese hamster ovary (CHO) cells but did not abolish (only partly reduced) virus binding to CHO cells that also express CAR (CAR-expressing CHO cells). When compared to original CHO cells, HAdV-G52 showed a remarkable increase in binding to CAR-expressing CHO cells [140]. Thus, HAdV-G52 may use its long or short fiber knob or both knobs for attachment to host CAR and/or Sia as a primary receptor or co-primary receptors to initiate virus infection.…”
Section: Adenoviridaementioning
confidence: 99%
“…The ionic interactions between the virion and cell surface glycosphingolipids aid a number of enveloped and non-enveloped viruses in their entry, as the adhesion of virions to cell membrane permits them to be recognized by the specific internalization receptors [115]. For instance, the infection of subgroup D viruses of adenoviruses occurs after binding to α (2-3)-linked sialic acid (SA), a common carbohydrate component of glycolipids [116], and uses a positive feedback loop between virus uncoating and lipid signaling for efficient membrane penetration [117]. Many RNA viruses and some DNA viruses use lipids such as low-density lipoprotein receptors (LDLR), phospholipids, and gangliosides for entry [118].…”
Section: Lipogenesismentioning
confidence: 99%